(untitled) (Research, Society and Development, 2021)
This paper aims to identify the barriers that are related to the maturity of project management in the public sector. Therefore, a systematic literature review was carried out based on works extracted from the CAPES Journal Portal and Google Scholar, using the protocol proposed by Felizardo et al. (2017) and from the keywords “project management maturity”, “public-sector”, “barriers” and their variations. The final review sample consisted of six studies, two of which were developed in the Brazilian context, one in the United Kingdom, one in Slovenia, one in Serbia, and one in Iceland. The barriers presented in the studies were summarized in seven dimensions: technical competence, management methodology, computerization, human relations, organizational structure, alignment with the organization’s business, and transversal categories. The notes of the studies brought as main notes the needs that organizations work with the intensification of benchmarking practices in the context of project management and the integration of this area with its strategic management.